Influence of Culture on Entrepreneurial Orientation and Performance of Nigerian Firms - Udeozor, Victor Chukwuemeka (2011)
The influence of culture on entrepreneurship has continued to attract scholarly interest and empirical scrutiny for the last two decades. Some international researches have explored the effect of national culture on entrepreneurial orientation (EO). Researchers have also explored the effect of EO on performance. However the inconsistencies in the findings of these studies have exposed the ambiguity of the relationships. Part of the reason for these inconsistencies, is in the treatment of EO. Most studies take a gestalt approach while a few recent ones take a component level approach which examines the independent relationship of the dimensions of EO with culture and with performances respectively. The other part of the reason for inconsistencies, is the context in which the studies where made. Just as Lumpkin and Dess (1996) cautioned, the EO-performance relationship has been found to be context specific. Until now, no empirical study of the effect of the five dimensions of EO on performance in the Nigerian context has been made. This study addresses the inconsistences by extending the knowledge on the influence of culture on the five dimensions of EO and the effect of the five dimensions of EO on firms’ performance to the Nigerian context. Data was collected from 47 firms located and operating in Nigeria and analysed. The first part of the results shows that culture does not affect innovativeness; it significantly affects risk taking and autonomy but does not significantly affect proactiveness and competitive aggressiveness; the second part shows that culture has no direct impact on performance; the third part, which supports the concerns of Lumpkin and Dess (1996) and is largely consistent with the result of Hughes and Morgan, (2007), shows that only innovativeness has a positive relationship with firms’ performance; proactiveness, competitive aggressiveness and autonomy have no effect while risk taking has a negative relationship with performance. From these results, managerial implications and recommendations for future research was offered.